Roasted Chickpeas as a Probiotic Carrier to Improve L. Plantarum 299v Survival During Storage - Paredes-Toledo, J (ELSEVIER, 2021)
Probiotic incorporation in non-dairy food may be a good strategy to extend shelf-life and diversify probiotic sources, and a new approach could be the use of consumable seeds as probiotic carriers. In this work, almonds, pumpkin seeds, and roasted chickpeas were immersed in L. plantarum 299v and L. rhamnosus GG dispersions and dried at 42 degrees C. Immediately after drying, seeds with L. rhamnosus GG had less than 7 log CFU/g in all seeds, while with L. plantarum 299v had higher cell counts than the minimum recommended (7 log CFU/g), showing a good probiotic absorption efficiency. After 3 months of storage, roasted chickpeas were able to protect L. plantarum 299v as its survival was 9.23 log CFU/g at 4 degrees C, and 7.30 log CFU/g at 25 degrees C, showing it could be a good candidate to use as a carrier to extend the shelf-life of this specific strain.